Preparation method and application of dual fluorescence resonance energy transfer light capture nanofiber
By constructing a dual fluorescence resonance energy transfer system and electrospinning technology in nanofibers, the limitations of traditional photocatalysts in light capture efficiency, activity, spectral response and stability are solved, and efficient, stable and reusable photocatalysts are achieved.
Patent Information
- Application Number
- CN202411967724.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Traditional photocatalysts have limitations in light capture efficiency, photocatalytic activity, spectral response range, and stability and recyclability.
Using a dual fluorescence resonance energy transfer (FRET) system, a continuous two-step FRET system is constructed by introducing two energy donors and one acceptor fluorescent molecule into the nanofibers to improve the energy transfer efficiency, and a nanofiber membrane with high specific surface area and porosity is prepared through electrospinning technology.
The light capture efficiency and activity of the photocatalyst is significantly improved, the spectral response range is expanded, the light stability and reusability are enhanced, and a highly efficient, stable and reusable photocatalyst is provided.
Smart Images

Figure BDA0005218752680000041 
Figure BDA0005218752680000051 
Figure BDA0005218752680000052
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of a double fluorescence resonance energy transfer (FRET) light-harvesting nanofiber and its application in a photocatalytic reaction, belonging to the technical field of nanomaterials. Background Art
[0002] In the field of chemical synthesis and materials science, photocatalysts have attracted much attention due to their potential applications in environmental purification, energy conversion, and organic synthesis. These catalysts absorb light energy to excite electrons, trigger chemical reactions, and achieve substrate conversion. However, traditional photocatalysts have many limitations, including low light harvesting efficiency, insufficient photocatalytic activity, limited spectral response range, and poor stability and recyclability. These limitations affect the practical application efficiency and economy of photocatalysts.
[0003] To overcome these challenges, researchers have explored fluorescence resonance energy transfer (FRET) technology to improve the light-harvesting efficiency and activity of photocatalysts. FRET is a non-radioactive energy transfer process that enables efficient energy transfer between donor fluorescent molecules and acceptor fluorescent molecules. However, ordinary FRET and single FRET systems usually involve a single energy transfer step, which may lead to low energy transfer efficiency, especially when the distance between the donor and the acceptor is far. Moreover, these systems can usually only effectively utilize light energy within a specific wavelength range, limiting their application under wide-spectrum light sources. Due to the poor photostability and reproducibility of fluorophores, these systems are prone to photobleaching under long-term illumination, affecting catalytic efficiency and reusability. In addition, the extinction cross-section of organic fluorophores is small, resulting in the need for higher light power to drive the reaction. Summary of the invention
[0004] The technical problem to be solved by the present invention is that traditional photocatalysts are limited in light capture efficiency, photocatalytic activity, spectral response range, stability and recyclability.
[0005] In order to solve the above problems, the present invention provides a method for preparing a dual fluorescence resonance energy transfer light-harvesting nanofiber, comprising the following steps:
[0006] Step 1): adding deionized water to polyvinyl alcohol (PVA) and a cationic polymer and stirring to fully swell the polyvinyl alcohol; then sealing the obtained mixture and placing it in a water bath for heating and stirring until the polyvinyl alcohol is fully dissolved to obtain a transparent and uniform polyvinyl alcohol aqueous solution, and after cooling the solution, a cationic polyvinyl alcohol electrospinning solution is obtained;
[0007] Step 2): adding three fluorophores, tetraphenylethylene sulfonate (TPE4S), acid yellow 184 (AY184) and fluorescent pink B (PhB) into the cationic polyvinyl alcohol electrospinning solution to obtain a fluorescent polyvinyl alcohol spinning solution;
[0008] Step 3): The fluorescent polyvinyl alcohol spinning solution is transferred into a syringe, and spinning is performed using a uniaxial electrospinning device. The nanofibers are collected using a roller coated with silicone oil paper, and the obtained nanofibers are dried in a blast drying oven.
[0009] Preferably, in step 1), the degree of polymerization of polyvinyl alcohol is 1750, and the degree of alcoholysis is 88%; the cationic polymer is at least one of polydiallyl dimethyl ammonium chloride (PDADMAC) and polyethyleneimine.
[0010] More preferably, the molecular weight of the polydiallyl dimethyl ammonium chloride is 5000-200000; the polyethylene imine is hyperbranched polyethylene imine or linear polyethylene imine, and the molecular weight is 300-2000.
[0011] Preferably, in step 1), the ratio of polyvinyl alcohol, cationic polymer and deionized water is 5-10 g: 0-1 g: 90-95 mL.
[0012] Preferably, in step 1), the temperature of the water bath is 80-100° C., and the heating and stirring time is 5 hours.
[0013] Preferably, in step 2), the dosage of the three fluorophores is 2.4×10 -4 -2.4×10 -5 mol / g.
[0014] Preferably, in the step 2), the spinning process parameters are: voltage 12 kV, receiving distance 15 cm, flow rate 0.4 mL / h, drum speed 300 rpm; drying temperature 50° C., time 12 h.
[0015] The present invention also provides the use of the double fluorescence resonance energy transfer light-harvesting nanofiber prepared by the above preparation method as a photocatalyst in a photocatalytic reaction.
[0016] Preferably, the photocatalytic reaction is a cross-coupling dehydrogenation (CDC) reaction between an N-phenyl-tetrahydroisoquinoline derivative and dimethyl phosphite, nitromethane or acetone.
[0017] Preferably, the dual fluorescence resonance energy transfer light harvesting nanofibers are used for multiple photocatalytic reactions after being washed with a solvent.
[0018] The principle of the present invention is as follows:
[0019] (1) Continuous two-step FRET system: The present invention significantly improves the energy transfer efficiency by constructing a continuous two-step FRET system. By introducing two energy donors (TPE4S and AY184) and one acceptor (PhB) into the nanofibers, efficient energy transfer is achieved.
[0020] (2) Carriers with high specific surface area and porosity: The nanofiber membrane prepared by electrospinning technology has a high specific surface area and porosity, which provides abundant sites for photocatalytic reactions and improves the reaction rate.
[0021] (3) Enhanced photostability and reproducibility: By fixing the fluorophore on the cationic PVA fiber, the photobleaching of the fluorophore is reduced, and the photostability and reusability are improved.
[0022] (4) Broad spectral response: By designing a FRET system with a broad spectral response, the present invention can effectively utilize a broad spectrum light source and improve the photocatalytic efficiency.
[0023] Through the above innovative ideas, the present invention not only solves the problems existing in ordinary FRET and single FRET systems, but also provides an efficient, stable and reusable photocatalyst suitable for a variety of photocatalytic reactions.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The photocatalytic fiber of the present invention utilizes the dual FRET effect and the aggregated luminescence effect of the donor to significantly improve the photocatalytic performance, and is particularly suitable for the cross-coupling dehydrogenation (CDC) reaction between N-phenyl-tetrahydroisoquinoline derivatives and phosphites.
[0026] (2) The photocatalyst of the present invention has high photocatalytic activity, good substrate universality and excellent cyclic stability, providing an efficient and sustainable solution for photocatalytic reactions. DETAILED DESCRIPTION
[0027] In order to make the present invention more clearly understood, preferred embodiments are described in detail as follows.
[0028] The present invention provides a method for preparing a dual fluorescence resonance energy transfer (FRET) light-harvesting nanofiber, comprising the following steps:
[0029] a. Preparation of raw materials and reagents: tetraphenylethylene tetrasulfonate (TPE4S); acid yellow 184 (AY184); fluorescent pink B (PhB); polyvinyl alcohol (PVA, molecular weight 75,000); polydimethylammonium chloride (PDADMAC, molecular weight 100,000-200,000); silver trifluoroacetate; polyvinyl pyrrolidone (PVP); ethylene glycol (EG); other conventional chemical reagents.
[0030] b. Preparation of electrospun nanofibers: 10 g of PVA and different contents of PDADMAC were added to 90 mL of deionized water, stirred for 30 minutes to fully swell, and heated in a water bath at 80°C for 5 hours to obtain a transparent and uniform PVA aqueous solution.
[0031] c. Preparation of light-harvesting nanofibers: Add three fluorophores, TPE4S, AY184 and PhB, to the PVA electrospinning solution, stir magnetically for 3 hours at room temperature, transfer to a syringe, and spin using a uniaxial electrospinning device at 12 kV, 15 cm working distance and 0.4 mL / h flow rate. Collect the nanofibers using a roller coated with silicone oil paper. Dry the obtained nanofibers in a 50°C forced air drying oven for 12 hours, seal and place in a backlit place for later use.
[0032] d. Application of photocatalytic CDC reaction: The reactants N-phenyl-tetrahydroisoquinoline or its derivatives (0.1mmol) and phosphite (0.2mL) were dissolved in 10mL ethanol and placed in a 20mL quartz tube. The prepared light-harvesting nanofiber membrane was cut into 1cm×1cm squares and immersed in the above reaction solution. Under the simultaneous irradiation of 1W white light LED and 365nm ultraviolet light LED, the reaction was kept warm for 4 hours. Samples were taken every 0.5 hours, and the conversion rate of N-aryl-tetrahydroisoquinoline at different times was monitored by HPLC.
[0033] The TPE4S-AY184-PhB / Ag / PDADMAC / PVA nanofibers prepared by the above steps exhibited excellent photocatalytic performance in the CDC reaction, with high conversion rate and good cycle stability.
[0034] Example 1: Effect of PDADMAC / PVA composite nanofibers with different cationization levels on the fixation of fluorophores
[0035] The cationization level of the composite nanofiber membrane was controlled by changing the mass fraction of PDADMAC relative to PVA. First, five groups of PDADMAC / PVA aqueous solutions with different PDADMAC contents were prepared, wherein the mass fraction of PVA was 10%, and the mass fraction of PDADMAC relative to PVA was 0%, 3%, 5%, 7%, and 10%; the above mixed aqueous solutions were used as spinning solutions for electrospinning, and the Zeta potential of the obtained nanofibers was tested, and the test results are shown in Table 1.
[0036] Table 1
[0037] Mass fraction of PDADMAC relative to PVA (%) Zeta potential (mV) 0 -1.86 3 2.45 5 5.12 7 8.84 10 12.65
[0038] Take 10 g of PDADMAC / PVA aqueous solution with 0%, 5%, and 10% PDADMAC content in three groups, and add 2.4×10 -4 mol of three fluorophores, TPE4S, AY184, and PhB, were prepared by spinning nanofiber membranes, and then the adsorption and fixation rates of the composite fiber membranes for the three fluorophores were determined by desorption experiments. The desorption experiment was to weigh 0.25g of the above fiber membranes and place them in 100mL of ethanol for 5 times for 6 hours, and the final adsorption and fixation rate was determined by measuring the final absorbance. The data results are shown in Table 2.
[0039] Table 2
[0040]
[0041]
[0042] Example 2: Optimization of the ratio between the three fluorophores when the fluorescence effect of the main catalyst PhB is optimal
[0043] A spinning solution with a relative PDADMAC content of 10% was selected to first determine the optimal ratio of energy transfer from TPE4S to AY184 in the first step; then, based on this, different amounts of PhB were added to determine the ratio between the three fluorophores when the fluorescence effect of the main catalyst PhB (which can be considered as the catalytic effect) was optimal.
[0044] The amount of the first donor TPE4S was 2.4×10 -4 mol / g polyvinyl alcohol, adding different contents of the second donor AY184, and preparing five different molar ratios of one-step FRET light-trapping nanofibers by electrospinning. By comparing the height of the AY184 fluorescence emission peak, the optimal ratio between the two in the first step FRET was determined. The obtained data results are shown in Table 3.
[0045] Table 3
[0046]
[0047] In the first step of FRET, the molar ratio of TPE4S to AY184 that is most conducive to FRET is 10:1. Based on this ratio, different amounts of the main catalyst and the acceptor fluorophore PhB are added to determine the amount of each dye at the optimal ratio. That is, the amount of TPE4S is 2.4×10 -4 mol / g polyvinyl alcohol, the dosage of AY184 is 2.4×10 -5 mol / g polyvinyl alcohol. By comparing the height of the fluorescence emission peak of PhB, the optimal amount of PhB in the second step FRET was determined. The obtained data results are shown in Table 4.
[0048] Table 4
[0049]
[0050]
[0051] As can be seen from Table 4, the optimal molar ratio between the three fluorophores is 10:1:1.
[0052] Example 4: Universal applicability of light-harvesting nanofibers to substrates in photocatalytic CDC reactions
[0053] The capture nanofibers with the best ratio of three fluorophores were prepared by electrospinning as photocatalysts, and their universality in catalyzing the CDC reaction of N-phenyl-tetrahydroisoquinoline derivatives with dimethyl phosphite or diethyl phosphite was studied. Reaction conditions: N-phenyl-tetrahydroisoquinoline (0.1mmol), dimethyl phosphite or diethyl phosphite (0.2mL), 50mg light-trapping nanofiber membrane (PhB, 1.2mol%), 10mL ethanol, temperature 35℃, time 4h, 1W white light + UV LED irradiation. The data results are shown in Table 5.
[0054] Table 5
[0055] N-Phenyl-tetrahydroisoquinoline derivatives Phosphites Substrate conversion rate (%) N-(4-Methylphenyl)-tetrahydroisoquinoline Dimethyl phosphite 93.8 N-(4-Methoxyphenyl)-tetrahydroisoquinoline Dimethyl phosphite 91.6 N-(4-Chlorophenyl)-tetrahydroisoquinoline Dimethyl phosphite 96.6 N-(4-Trifluoromethoxy)phenyl-tetrahydroisoquinoline Dimethyl phosphite 93.7 N-(4-Methylphenyl)-tetrahydroisoquinoline Diethyl phosphite 90.2 N-(4-Methoxyphenyl)-tetrahydroisoquinoline Diethyl phosphite 87.1 N-(4-Chlorophenyl)-tetrahydroisoquinoline Diethyl phosphite 93.8 N-(4-Trifluoromethoxy)phenyl-tetrahydroisoquinoline Diethyl phosphite 89.8
[0056] Example 5: Cyclic stability of light-harvesting nanofibers in photocatalytic CDC reactions
[0057] The capture nanofibers with the best ratio of three fluorophores were prepared by electrospinning. The CDC reaction between N-phenyl-tetrahydroisoquinoline and dimethyl phosphite was used as a model to study the cyclic stability of the light-harvesting nanofibers in the photocatalytic CDC reaction. Reaction conditions: N-phenyl-tetrahydroisoquinoline (0.1mmol), dimethyl phosphite or diethyl phosphite (0.2mL), 50mg light-harvesting nanofiber membrane (PhB, 1.2mol%), 10mL ethanol, temperature 35℃, time 4h, 1W white light + UVLED irradiation. The data results are shown in Table 6.
[0058] Table 6
[0059] Cycle times Substrate conversion rate (%) 1 99.6 2 97.1 3 94.4 4 93.8 5 93.3
Claims
1. A method for preparing a dual fluorescence resonance energy transfer light-harvesting nanofiber, characterized in that: The following steps are involved: Step 1): adding deionized water to polyvinyl alcohol and cationic polymer and stirring to fully swell them; then sealing the obtained mixture and placing it in a water bath for heating and stirring until the polyvinyl alcohol is fully dissolved to obtain a transparent and uniform polyvinyl alcohol aqueous solution, and after cooling, a cationic polyvinyl alcohol electrospinning solution is obtained; Step 2): adding three fluorophores, tetrasulfonated tetraphenylethylene, acid yellow 184 and fluorescent pink B, to a cationic polyvinyl alcohol electrospinning solution to obtain a fluorescent polyvinyl alcohol spinning solution; Step 3): The fluorescent polyvinyl alcohol spinning solution is transferred into a syringe, and spinning is performed using a uniaxial electrospinning device. The nanofibers are collected using a roller coated with silicone oil paper, and the obtained nanofibers are dried in a blast drying oven.
2. The method for preparing the dual fluorescence resonance energy transfer light-harvesting nanofiber according to claim 1, characterized in that: In the step 1), the degree of polymerization of polyvinyl alcohol is 1750, and the degree of alcoholysis is 88%; the cationic polymer is at least one of polydiallyl dimethyl ammonium chloride and polyethylene imine.
3. The method for preparing the dual fluorescence resonance energy transfer light-harvesting nanofiber according to claim 2, characterized in that: The molecular weight of the polydiallyl dimethyl ammonium chloride is 5000-200000; the polyethylene imine is hyperbranched polyethylene imine or linear polyethylene imine, and the molecular weight is 300-2000.
4. The method for preparing the dual fluorescence resonance energy transfer light-harvesting nanofiber according to claim 1, characterized in that: In the step 1), the ratio of polyvinyl alcohol, cationic polymer and deionized water is 5-10 g: 0-1 g: 90-95 mL.
5. The method for preparing the dual fluorescence resonance energy transfer light-harvesting nanofiber according to claim 1, characterized in that: In the step 1), the temperature of the water bath is 80-100° C., and the heating and stirring time is 5 hours.
6. The method for preparing the dual fluorescence resonance energy transfer light-harvesting nanofiber according to claim 1, characterized in that: In step 2), the dosage of the three fluorophores is 2.4×10 -4 -2.4×10 - 5 mol / g.
7. The method for preparing the dual fluorescence resonance energy transfer light-harvesting nanofiber according to claim 1, characterized in that: In the step 2), the spinning process parameters are: voltage 12 kV, receiving distance 15 cm, flow rate 0.4 mL / h, drum speed 300 rpm; drying temperature 50° C., time 12 h.
8. Use of the double fluorescence resonance energy transfer light-harvesting nanofiber prepared by the preparation method according to any one of claims 1 to 7 as a photocatalyst in a photocatalytic reaction.
9. The use according to claim 8, characterized in that The photocatalytic reaction is a cross-coupling dehydrogenation reaction between N-phenyl-tetrahydroisoquinoline derivatives and dimethyl phosphite, nitromethane or acetone.
10. The use according to claim 8 or 9, characterized in that: The dual fluorescence resonance energy transfer light-harvesting nanofiber is used for multiple photocatalytic reactions after being washed with a solvent.
Citation Information
Patent Citations
Preparation method of flexible white fluorescence nanometer fiber membrane
CN108265400A
Reversible humidity-responsive fluorescent discoloration system as well as preparation method and application thereof
CN115723457A
Continuous light capturing system, preparation method and application of continuous light capturing system in photocatalytic oxidation
CN119034806A
Preparation method for nanocomposite fiber membrane material based on bio-based liquefied formaldehyde resin
US12161995B1
Biodegradable graphene oxide biocomposite fibrous membrane, preparation method and uses thereof
US20200330641A1